Diversity Enhancement of MIMO System with GA Optimized Linear Precoding of Orthogonal Space-Time Block Codes - Harsha Gurdasani; A G Ananth; N Thangadurai (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
The MIMO (Multiple-Input Multiple-Output) systems in the field of digital communications make it possible to improve data transmission according to two main parameters which are often antagonistic: the information rate and the transmission reliability estimated in average binary error probability (BEP) term. With such systems, CSI (Channel State Information) on transmission is a key point for reducing the BEP thanks to different power allocation strategies. Thus, a linear precoder on transmission associated with a linear decoder on reception can optimize a particular criterion thanks to this information. This paper proposes a MIMO system with precoded orthogonal space-time block codes (OSTBC) optimized by Genetic Algorithm with ZF and MMSE equalization. The performance evaluation is achieved by BER vs. SNR graphs.